2021
DOI: 10.1002/jca.21885
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell mobilization in multiple myeloma patients relapsing after previous autologous hematopoietic stem cell transplantation: A multicenter report by the Polish Myeloma Study Group

Abstract: Background Salvage autologous hematopoietic stem cell transplantation (autoHSCT) may be used to treat relapse of multiple myeloma occurring after previous autoHSCT. When insufficient number of hematopoietic stem cells was stored from the initial harvest, remobilization of stem cells is necessary. Purpose The analysis of stem cell remobilization after previous autoHSCT. Patients and Methods Fifty‐eight patients, 60% males, median 59 years, were included. Median time interval between autoHSCT and remobilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
3
1
Order By: Relevance
“…The results of the EAP regimen were encouraging as it was shown to be well tolerated with a low incidence of grade 2–3 infections. In addition, the incidence of grade 3–4 haematological adverse events was similar or lower to that reported for other chemo‐based mobilization treatments 11,20,21 . However, these cross‐trial comparisons should be interpreted with caution as 43.1% of our patients required platelet transfusions, with the rate of these transfusions being higher than those reported by other studies 11,22 .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The results of the EAP regimen were encouraging as it was shown to be well tolerated with a low incidence of grade 2–3 infections. In addition, the incidence of grade 3–4 haematological adverse events was similar or lower to that reported for other chemo‐based mobilization treatments 11,20,21 . However, these cross‐trial comparisons should be interpreted with caution as 43.1% of our patients required platelet transfusions, with the rate of these transfusions being higher than those reported by other studies 11,22 .…”
Section: Discussionsupporting
confidence: 76%
“…In addition, the incidence of grade 3-4 haematological adverse events was similar or lower to that reported for other chemo-based mobilization treatments. 11,20,21 However, these cross-trial comparisons should be interpreted with caution as 43.1% of our patients required platelet transfusions, with the rate of these transfusions being higher than those reported by other studies. 11,22 This finding can be explained by the poor mobilizers requiring more platelet transfusions and the combined use of etoposide and cytarabine.…”
Section: Discussioncontrasting
confidence: 59%
“…The protocol with cytarabine demonstrated better efficacy and acceptable toxicity [18]. The same authors showed the effectiveness of remobilization regimen with cytarabine after the previous auto-HSCT [19].…”
Section: Discussionmentioning
confidence: 88%
“…In this situation, our data would support the addition of antibiotics prophylaxis to decrease infection risk. Cyclophosphamide has also been used in stem cell remobilization in relapsed myeloma for salvage transplant, in patients who may have previously received intensive therapy, as reported by Baertsch et al and Drozd-Sokolowska et al 22,23 It may have an ongoing role in this setting, although both authors reported infectious complications from this approach. Notably, Basak et al and Khaled et al have reported on the effectiveness of plerixafor in the remobilization setting, with omission of mobilizing chemotherapy.…”
Section: Discussionmentioning
confidence: 98%